Peran Mediasi Green Innovation Pada Pengaruh Human Capital Terhadap Kinerja Bisnis UMKM Surabaya - Ula, Fitrotul; Khusnah, Hidayatul; Anugraini, Mardiyah; Anshori, Mohamad Yusak (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2023)
The purpose of this study was to determine the effect of the mediating role of green innovation on the influence of human capital on business performance in MSMEs in Surabaya. The population in this study were all MSMEs in Surabaya in the accommodation and food and beverage provider sector, while the samples were taken using purposive sampling with special criteria, namely MSMEs that had been operating for more than 1 year. The data collection method uses a questionnaire in the form of a Google form and is distributed online to respondents. The number of respondents who met the criteria in the study were 100 respondents. This study uses the WarpPLS 8.0 application to assist in analyzing. The data analysis technique used is the outer model (validity test and reliability test), inner model (determinant coefficient, Q-squared and effect size), and hypothesis testing. The empirical results of this study indicate that human capital has a positive and significant effect on business performance and green innovation. Green innovation has a positive and significant effect on business performance. Furthermore, green innovation is able to mediate human capital on business performance.